(untitled) (Medical Forum Monthly, 2024)
Purpose: To study the effect of Bevacizumab and Bevacizumab combined with Macular Grid on diabetic macular oedema. Study Design: Prospective study Place and Duration of Study: This study was conducted at the Multan Medical and Dental College, Multan and Bodla Eye Care, Multan. from January 2014 to June 2014. Materials and Methods: A prospective study from South Punjab that included 18 patients (36 eyes) with diffuse diabetic macular oedema. In every patient one eye was treated with a series of three Bevacizumab injections 5 weeks apart and other eye with a series of three injections of Bevacizumab, 5 weeks apart combined with macular grid on fourth week after first injection. Patient had a detailed ophthalmic assessment prior to recruitment and during the course of study on every visit. Patient had an optical coherence tomography measuring retinal thickness prior to start of the treatment and on subsequent visits. Endpoint was considered as five months from the start of treatment during which patients had a regular follow up. Results: Comparison was made between two groups taking into account visual acuity and central macular thickness as the primary measures. The difference between the mean central macular thickness at the time of enrollment and post study was statistically significant (P<0.05) in both groups. There was no statistically significant improvement in visual acuity (P>0.05) between the two groups or difference in mean reduction of retinal thickness (P>0.05). Visual acuity was assessed in terms of mean gain, maintained or lost vision. Conclusion: Bevacizumab does reduce the retinal thickness i.e. reduction in macular oedema in diabetics. However combining it with macular grid failed to show any statistically significant difference in terms of improvement in visual acuity or reduction in mean central retinal thickness.